Recovery of High Molecular Weight DNA from Old viscera Samples via Two Established Methods for Human Identification: A Comparative Study (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
At autopsy, in cases of suspected poisoning or drug intoxication, the viscera are mostly preserved in saturated common salt solution for toxicological analysis. However, frequent situation arises where the preserved viscera sample gets questioned for its source of origin and identification of the individual contributing the said viscera becomes important. In such a scenario, to identify the source of viscera, the DNA Profiling technique can be employed. This study aims at recovery of high molecular weight DNA suitable for DNA profiling from a 5-year-old viscera sample through modified validated methods. Approximately 2 g of viscera samples (kidney) were taken for the study and two different established DNA extraction methods were employed for isolating DNA for downstream procedures viz. quantitation of the extracted DNA, the amplification of the desired loci Polymerase chain reaction (PCR) and its subsequent genotyping. The yield of DNA extracted from both the methods was quantitated using real time PCR system and a complete DNA profile was obtained for the purpose of comparison with the biological relatives of the individual.
Keywords: Viscera; PCR amplification; DNA profiling; Organic extraction; Extraction using EZ1 bio-robot